VD_FINDINFO Décision / 2015 / 348 vom 5. Mai 2015 - VD Tribunal cantonal (2015)
LIBÉRATION CONDITIONNELLE, INTERNEMENTDROIT PÉNAL, INDEMNITÉEN GÉNÉRAL, AVOCAT D'OFFICE, FRAIS DE VOYAGE | 64 CP, 38 LEP, 135 CPP (CH), 393 CPP (CH)